Republic of Kazakhstan : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2021)
The mission welcomes the progress made by the RK in improving the quality of GFS. The Ministry of Finance has taken into account several recommendations of the previous mission on increasing transparency, improving data quality, and regarding the channels used to provide GFS. In particular, updated bridge tables are used when generating statistics, National Fund (NF) data are recorded separately from national budget (NB) data, and GFS are disseminated through the IMF Integrated Data Collection System.